Communicative Approach to Teaching Foreign Languages - Korol’, Svitlana (Pedagogical Discourse, 2012)
The article deals with communicative method of teaching foreign languages, communicative competence as a result of such teaching. The advantages and disadvantages of communicative teaching are determined.